Indigenous Knowledge - Cross - Regional Distance Learning Course (India, Sri Lanka, Uganda and Tanzania) - Prakash, Siddhartha (World Bank, Washington, DC, 2012)
Indigenous knowledge (IK) is usually shared among local communities and transferred from one generation to the next, through oral traditions and story-telling. The IK distance learning course was an effort to facilitate this process across four countries and two continents. Information communications technology (ICTs) enabled the bridging of the geographical and perceptional distance between the 102 participants, through the videoconference facilities of the global development learning network. The course effectively demonstrated how leveraging traditional and modern knowledge systems can help address development challenges.